Can robots help the learning of skilled actions? - Reinkensmeyer, D. J.; Patton, J. L. (Exercise and Sport Sciences Reviews, 2009)
Learning to move skillfully requires that the motor system adjusts muscle commands based on ongoing performance errors, a process influenced by the dynamics of the task being practiced. Recent experiments from our laboratories show how robotic devices can temporarily alter task dynamics in ways that contribute to the motor learning experience, suggesting possible applications in rehabilitation and sports training.